Про визначення поняття «платіжна система» в контексті змін чинного законодавства України - Ковальчук, А. С. (НДІ ПЗІР НАПрН України, 2022)
Підвищення вартості безготівкових розрахунків та посилення ролі неоднорідних платіжних систем за останні роки, особливо в умовах карантину, пов’язаних із коронавірусною хворобою COVID-19, стало чіткою та безумовною тенденцією у сфері економічних відносин. Глибокі зміни в організації розрахунків, викликані швидким розвитком інформаційно-телекомунікаційних технологій, а також процесами глобалізації, призводять до необхідності нових наукових досліджень з проблем правового регулювання платіжних систем, оскільки, на жаль, теоретичні досягнення у цій сфері втрачають свою актуальність через високу динаміку мінливих економічних і соціально-політичних умов. На цьому тлі останні зміни в чинному законодавстві України потребують їх детального аналізу та усвідомлення, а отже, перегляду деяких фундаментальних поглядів, зокрема визначення поняття «платіжна система» У наукових колах ведеться широка дискусія щодо визначення поняття «платіжна система» до цих пір остаточно не вирішило таку проблему. Спроби подолати розбіжності у визначенні сутності поняття «платіжна система» в загальному розумінні не призвели до уніфікації існуючих наукових підходів. Водночас такі теоретичні пошуки дали можливість оцінити явище з точки зору уявлень про його сутність, зміст і форму. У статті розглядається проблема визначення поняття «платіжна система» в умовах докорінної зміни спеціального законодавства України з питань організації розрахункових відносин. Наголошується на відсутності загальновизнаного наукового підходу у питанні про визначення поняття та сутності платіжної системи, підкреслюється наявність широкої дискусії з такої проблеми. Звертається увага на зміщення акценту у визначенні сутності платіжної системи з переказу коштів на надання платіжних послуг. Пропонується авторське визначення платіжної системи як правової форми надання платіжних послуг. Problem setting. Increasing the value of cashless payments and strengthening the role of heterogeneous payment systems in recent years, especially in the conditions of quarantine restrictions related to the coronavirus disease of COVID19, has become a clear and unconditional trend in the field of economic relations. Profound changes in the organization of calculations caused by the rapid development of information and telecommunication technologies, as well as the processes of globalization, lead to the need for new scientific research on the problems of legal regulation of payment systems, since, unfortunately, theoretical achievements in this area lose their relevance due to the high dynamics of the changing economic and socio-political conditions. Against this background, recent changes in the current legislation of Ukraine require their detailed analysis and awareness, and therefore the revision of certain fundamental views, including the definition of the concept of “payment system.” Analysis of resent researches and publications. The study of payment systems as an immanent component of the economic sphere has its own history and specifics. They were studied both from the position of economic theory, and became the subject of scientific searches of representatives of legal science. Some issues of essence, organization and functioning of modern payment systems have been the subject of scientific interest as domestic, and foreign economists, including Woodford M., Gerasimova S., Grytsenko A.A., Gross D., Demkivskyi A.V., Issing O., Koval I.M., Lukyanov V.S., Movchan O.A., Olifirenko M.M., Senyshchiv P.M. Their theoretical achievements are the foundation of understanding the peculiarities of legal regulation of heterogeneous calculation relations in modern economy. Lay the foundations for creating a holistic theory of settlement legal relations, and also contribute to the formation of the concept of payment law. Target of research is to update the issue of the essence and concept of the «payment system,» as well as to highlight the peculiarities of the transformation of the defining features of such an object of legal regulation in the conditions of systemic changes in the special legislation of Ukraine. Article’s main body. The article considers the problem of defining the concept of “payment system” in the conditions of radical change of the special legislation of Ukraine on the organization of settlement relations. It emphasizes the lack of a generally accepted scientific approach in the question of determining the concept and essence of the payment system, emphasizes the presence of a broad discussion on such a problem. Attention is drawn to the shift of emphasis in determining the essence of the payment system from the transfer of funds to the provision of payment services. The author’s definition of the payment system as a legal form of payment services provision is proposed. Conclusions and prospects for the development. There is a wide discussion in scientific circles about the definition of the “payment system” until now has not finally solved such a problem. Attempts to overcome disagreements in determining the essence of the concept of “payment system” in the general sense did not lead to the unification of existing scientific approaches. At the same time, such theoretical searches provided an opportunity to evaluate the phenomenon from the perspective of ideas about its essence, content and form.
Keywords: безготівкові розрахунки; імплементація; платіжна система; платіжне середовище; платіжні операції; платіжний ринок; переказ коштів; правова форма; cashless payments; implementation; payment system; payment environment; payment transactions; payment market; transfer of funds; legal form